AN INTEGRATIVE APPROACH TO MENOPAUSAL SYNDROME: A CASE STUDY COMBINING AYURVEDIC AND MODERN MANAGEMENT - Dr. Siddalingesh M. Kudari; Dr. Annapurna R. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Menopausal syndrome comprises a variety of physical, psychological, and emotional symptoms affecting women during the menopausal transition. This case study explores a detailed clinical scenario emphasizing symptomatology, diagnosis, therapeutic management, and outcomes associated with menopausal syndrome. Objective: To examine and present the clinical characteristics, diagnostic challenges, and effective management strategies for menopausal syndrome. Methods: A detailed analysis of a 50-year-old woman presenting with hot flashes, insomnia, mood swings, and irregular menstruation was conducted. Diagnostic assessments included hormonal profiling, clinical examination, and psychosocial evaluations. The management approach included hormone replacement therapy (HRT), lifestyle modifications, dietary adjustments, and counseling. Results: Post-management, the patient exhibited significant improvement in symptoms including reduced frequency and intensity of hot flashes, improved sleep quality, stabilization of mood, and overall enhanced quality of life. Hormonal profiles showed normalization of estrogen levels post-treatment. Conclusion: Comprehensive management involving hormone replacement, lifestyle intervention, and psychological support effectively alleviates menopausal syndrome symptoms, significantly improving patient well-being.